Artistic Features and Issues in the Realistic Stories of A. Arcishevsky (Eurasian Journal of Philology Science and Education, 2025)
This article analyzes the poetics and issues of the realistic stories of the contemporary Kazakhstani writer Adolf Arcishevsky. The main objective of this study is to identify the artistic uniqueness and thematic concerns of A. Arcishevsky's stories. The article examines the primary genre-related characteristics, artistic features, and thematic issues in his works. The theoretical significance of this research lies in its potential contribution to the study of realistic stories by contemporary Kazakhstani writers. The practical significance of the article is that its findings and conclusions can be used to develop methodological approaches for analyzing A. Arcishevsky's stories in higher education.  A poetic-structural method was applied to identify and analyze the artistic features and narrative structure of A. Arcishevsky's stories. The historical-literary approach helped establish the connection between the writer’s work and Russian realist literature. The analysis of the artistic language contributed to the characterization of the writer’s style.  In his stories, A. Arcishevsky realistically depicts the realities of Soviet life in the past century, recreating images of ordinary people. His works explore the problem of moral choice, portraying the unity of characters and their actions. Humanism serves as the ideological foundation of his stories, affirming the unconditional value of life and human personality. These characteristics align with the traditions of realist literature. The writer consistently develops the traditions of realism in his stories. Key words: contemporary Kazakhstani prose, short story, Kazakhstani short story, realism, A. Arcishevsky.